Nutritional Knowledge, Attitudes, and Practices of Women Living with HIV in Eastern Uganda - Bukusuba, John; Kikafunda, Joyce K; Whitehead, Roger G (Journal of Health, Population and Nutrition, 2010)
HIV and AIDS have posed various medical, nutritional, social and economic problems, female-headed households being the most affected. Poor nutritional knowledge and dietary practices common among the most affected households significantly contribute to the rapid progression of HIV. However, very little data exist concerning these aspects of nutrition among women living with HIV and AIDS in resource-limited settings, such as Uganda. The aim of the study was to investigate the gaps in nutritional knowledge, attitudes, and practices and their relationship with sociodemographic characteristics in an urban population of women living with HIV and AIDS in Uganda. In total, 133 women living with HIV were interviewed using a pretested questionnaire. Most (89.5%) women reported being trained on the importance of nutrition for people living with HIV and AIDS (PLWHA) and believed that it is very important to consume a balanced diet (99.5%). On the contrary, only 21.8% consumed at least three meals per day and 39.8% at least six food-groups. They also reported higher dependency on starchy staples while foods of animal origin and fruits that play vital immunity and protective roles were inadequately consumed. Results of bivariate analysis indicated that consumption of a diversified diet was significantly associated with access to food-aid (p=0.006), possibly because access to food-aid reportedly enhances the ability of the household to access other food items. However, much is still needed to understand the drug-food interaction and dietary diversification and enhance proper dietary practices through sustainable projects that ensure increased access to food. Support groups of the PLWHA are a good vehicle for communication of nutrition information and implementation of nutrition-related projects. Key words: Acquired immunodeficiency syndrome; Cross-sectional studies; Diet; Human immunodeficiency virus; Knowledge, attitudes, practices; Nutrition; Uganda DOI: 10.3329/jhpn.v28i2.4890 J Health Popul Nutr 2010 Apr; 28(2): 182-188